2016
DOI: 10.1108/yc-04-2016-00596
|View full text |Cite
|
Sign up to set email alerts
|

A case study on shopping malls attributes for young consumers

Abstract: Purpose This study aims to determine the mall criteria that are the most crucial for the youth market by determining the winning brand in comparison to other offerings to understand what is required to gain a competitive advantage and to differentiate a mall from its rivals. Design/methodology/approach This study chose the Stochastic Multicriteria Acceptability Analysis-2 method to evaluate the mall preferences of young people. By using this method, the various criteria were evaluated for more than one alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 69 publications
1
6
0
3
Order By: Relevance
“…Interestingly, the physical atmosphere of a SM did not affect customers’ choices. This finding is in line with the previously reported low impact of a mall's physical features and its facilities on mall choices for young people (Can et al , 2016). Atmosphere is treated as a hygienic, while customers simply expect all malls to be hygienic and safe.…”
Section: Research and Managerial Implicationssupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, the physical atmosphere of a SM did not affect customers’ choices. This finding is in line with the previously reported low impact of a mall's physical features and its facilities on mall choices for young people (Can et al , 2016). Atmosphere is treated as a hygienic, while customers simply expect all malls to be hygienic and safe.…”
Section: Research and Managerial Implicationssupporting
confidence: 93%
“…Mall attractiveness is affected by the perception related to the range of available shops and the diversity of brands. Mall campaigns can affect mall choice (Can et al , 2016) and gifts and incentives can engage customers in word of mouth behavior. However, price is not always a decisive factor in shoppers' attractiveness.…”
Section: Research Frameworkmentioning
confidence: 99%
“…In a different study, Can et al (2016), identified several factors affecting mall attractiveness. The factors were mall loyalty programmes; traffic around the mall and parking facilities; facilities for disabled people; the quality of the mall locality; and the quality of mall visitors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because, chance of finding an item in a less popular shopping malls or less crowded shopping malls is higher [5]. This phenomenon indicates that consumer selecting a shopping mall depends of on many uncertain or probabilistic factors [6], so, ahead of time it is not easy to compute which shopping mall is best fit for customer ahead of time. However, with the help of uncertain or probabilistic data management, it is possible to compute customer choices with some certainty.…”
Section: Introductionmentioning
confidence: 99%